2001
DOI: 10.1021/jp0103878
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Simulated and Experimental Voltammograms Obtained for the [Fe(CN)6]3-/4- Couple in the Absence of Added Supporting Electrolyte at a Rotating Disk Electrode

Abstract: The voltammetric behavior of the [Fe(CN) 6 ] 3-/4couple at a glassy carbon rotating macrodisk electrode without added supporting electrolyte is shown to be in close to ideal agreement with the theory presented over a wide range of electrode rotation and scan rates when the concentration of electroactive species used is 50 mM. The influences of migration, uncompensated resistance, heterogeneous charge-transfer kinetics, and inhomogeneous diffusion are shown to be well modeled by a finite difference simulation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…Electroactive surface area (ESA) measurements for each microelectrode were done through cyclic voltammetry scans performed in 2.5 mol cm −3 K 4 [Fe(CN) 6 ] 0.1 m KCl solution, in the potential range from −1.0 to 0.4 V at a scan rate of 0.1 V s −1 . ESA was estimated according to the Randles–Sevcik equationinormalp= 2.69 × 105AD1/2n3/2υ1/2Cwhere i p is the reduction/oxidation peak current (A), n is the number of electrons contributing to the redox reaction, A is the area of the electrode (cm −2 ), D is the diffusion coefficient of Fe(CN) 6 4− in KCl solution (6.3 × 10 −6 cm 2 s −1 ), C is the concentration of the Fe(CN) 6 4− in the bulk solution (mol cm −3 ), and υ is the scan rate (V s −1 ). The measurements were performed in triplicate, the results were expressed as a mean ± standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…Electroactive surface area (ESA) measurements for each microelectrode were done through cyclic voltammetry scans performed in 2.5 mol cm −3 K 4 [Fe(CN) 6 ] 0.1 m KCl solution, in the potential range from −1.0 to 0.4 V at a scan rate of 0.1 V s −1 . ESA was estimated according to the Randles–Sevcik equationinormalp= 2.69 × 105AD1/2n3/2υ1/2Cwhere i p is the reduction/oxidation peak current (A), n is the number of electrons contributing to the redox reaction, A is the area of the electrode (cm −2 ), D is the diffusion coefficient of Fe(CN) 6 4− in KCl solution (6.3 × 10 −6 cm 2 s −1 ), C is the concentration of the Fe(CN) 6 4− in the bulk solution (mol cm −3 ), and υ is the scan rate (V s −1 ). The measurements were performed in triplicate, the results were expressed as a mean ± standard deviation.…”
Section: Methodsmentioning
confidence: 99%
“…In the meantime, the graph of E p =f(ln v ) gives two straight lines which have slopes equal to RT/(1–α)nF for the anodic peak and ‐RT/αnF for the cathodic peak, the electron‐transfer coefficient, α, was found as 0.47 (Figure S1C). By using the values of difference in anodic and cathodic peak potentials depending on scan rates between 50 to 500 mV s −1 and diffusion coefficient (6.5×10 −6 cm 2 /s) of potassium ferrocyanide in 0.1 M KCl, the average electron transfer rate constant, k s , for heterogeneous electron transfer was calculated by Nicholson's equation and found to be (1.85±0.57)×10 −3 cm/s, indicating that the electron transfer on MEL‐imp/MWCNT/PRE is much slower than on unmodified electrode . The results showed that adsorbed polymer network on electrode surface might obstruct to a certain extent the rate of electron transfer .…”
Section: Resultsmentioning
confidence: 99%
“…Under these conditions eqs. (9) and (13) are replaced by the well-known Butler-Volmer equations. Some results are shown in Figure 6.…”
Section: Resultsmentioning
confidence: 99%
“…There is a considerable interest in the investigation of the influence of supporting electrolyte on the mass transfer [1][2][3][4] and the charge transfer [5] on microelectrodes [6][7][8] and rotating disk electrodes [9,10]. These measurements can be also performed in the thin layer cells [11][12][13][14][15], particularly in those that operate without a reference electrode [16][17][18].…”
Section: Introductionmentioning
confidence: 99%